PRELIMINARY PLANNING OF A MINING ROAD IN AMPAH DISTRICT, EAST BARITO REGENCY, CENTRAL KALIMANTAN: A TOPOGRAPHIC SURVEY USING TOTAL STATION - Danar A.W Gautama; Slamet Winaryo; Tuah; Petrisly Perkasa; Mega Kurniawati (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
This study aims to present a preliminary planning of a mining road in Ampah District, East Barito Regency, Central Kalimantan, based on topographic survey data obtained using a Total Station. The survey was conducted along a ±10.971-meter alignment traversing an area characterized by undulating to hilly terrain. The Total Station was used to accurately acquire positional and elevation data along the alignment, which was then utilized to develop the longitudinal profile and cross-sections as the basis for the geometric road design. The survey results revealed natural ground elevation variations ranging from approximately ±15 meters to ±109 meters, with significant elevation adjustments required in several segments. The longitudinal profile indicated that most of the alignment would require fill operations, particularly at STA 3+258, 3+903, and 10+775, where fill depths exceeded 6 meters. Conversely, cut areas were also identified in the initial segments of the alignment, as shown by green indicators on the profile drawings. The horizontal geometric design involved 24 curves, incorporating geometric control points such as PC (Point of Curvature), PT (Point of Tangent), and PI (Point of Intersection), as well as spiral curves to ensure smooth directional transitions. Meanwhile, drainage systems and slope stabilization measures were addressed through technical cross-sectional designs at several critical points. Overall, the use of the Total Station in this study has proven effective in producing high-quality survey data that serves as an accurate foundation for the initial planning of the mining road. These findings support the development of an efficient alignment design, well-suited to the terrain conditions and operational requirements of mining activities.